Neonatal Infammatory Cytokines and Cerebral Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The association of inflammatory, autoimmune and coagulation factors with cerebral palsy (CP) was examined at the National Institutes of Health, Bethesda, MD, and the Immunochemistry Laboratory, George Washington University Medical Center, using dried, preserved neonatal blood spot specimens of 31 children enrolled in the California Birth Defects case-controlled study of spastic CP and compared to 65 control children.